2021
DOI: 10.1016/j.jpowsour.2021.230202
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the thermodynamics of the bromine electrode in concentrated solutions for improved parametrisation of hydrogen–bromine flow battery models

Abstract: A novel thermodynamic bromine electrode model is described and validated. • It is applied to describe the open-circuit voltage of a pilot-scale flow battery. • Polybromide formation constants are reevaluated at high electrolyte concentrations. • Mean activity coefficient of aqueous HBr up to 11 m between 0 and 70 • C is modelled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Another risk is the catalytic layer degradation when halogen crossover occurs through the separator. 67,69 That is possible to achieve an energy capacity of about 170 Wh kg −1 , whereas it is still much lower than that of lithium-ion batteries that limit their application, and halogens show insufficient solubility in water. Therefore, all lead to limitations on the value of the specific energy capacity and its development.…”
Section: Hydrogen-halogen Redox Flow Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…Another risk is the catalytic layer degradation when halogen crossover occurs through the separator. 67,69 That is possible to achieve an energy capacity of about 170 Wh kg −1 , whereas it is still much lower than that of lithium-ion batteries that limit their application, and halogens show insufficient solubility in water. Therefore, all lead to limitations on the value of the specific energy capacity and its development.…”
Section: Hydrogen-halogen Redox Flow Batterymentioning
confidence: 99%
“…66 Wlodarczyk et al explored the new concepts and models and developed the concentrated solutions for bromine cathode thermodynamics in HBRFB chemistry, which made polybromides formation concentrations up to 7.7 mol L −1 (HBr) and 3.85 mol L −1 (Br 2 ) and a significant impact on the open-circuit potential. 67 Chlorine RFB has appealing properties such as fast kinetics and high reduction potential. Wang et al reported chlorine RFB that reversibly processes electrolysis in NaCl aqueous solution with RuO 2 -TiO 2 @C, then Cl 2 is generated and transformed into the carbonaceous tetrachloride (CCl 4 ) (Fig.…”
Section: Hydrogen-halogen Redox Flow Batterymentioning
confidence: 99%